Análise experimental de um sistema de refrigeração cascata comercial com HFC e HFO/R744 - Queiroz, Marcus Vinícius Almeida (2022)
This study presents the use of alternative refrigerant and components for commercial refrigeration systems using a cascade subcritical CO2 refrigeration system. The main goal of this work aims to replace the HFC-134a, widely used commercially in cascade systems, for less environmentally impacting fluids (HFOs), guaranteeing the temperatures and cooling capacities of the system, thus comparing energy efficiency, and consequently the environmental impact. The experimental apparatus consists of a R744 reciprocating compressor and an electronic expansion valve that promotes the direct evaporation of CO2 inside a cold room (2.3m x 2.6m x 2.5m). The high temperature HT cycle consists of a reciprocating compressor for R134a, an electronic expansion valve, and an air-cooled condenser with the temperature controlled. It also has an intermediate plate heat exchanger LLSLHX, and another plate exchanger, which is at the same time the condenser for R744 and the evaporator for R134a, completing the configuration. Subsequently, a gas-cooler was installed in the low-temperature LT cycle. Finally, a direct drop-in was performed in the system, replacing the HT fluid with HFO-1234yf and HFO-513A. The energy analysis of the original system (R134a/R744) was performed for a range of condensing temperatures from 36 to 48 °C, with air temperatures inside the cold chamber from -20 to-5.2 °C, cooling capacities of 3.62 ± 0.01 to 3.75 ± 0.01 kW, and COP of 0.94 ± 0.02 to 1.06 ± 0.02. In the second stage, with the installation of a gas-cooler, a reduction in the air temperature inside the cold chamber of approximated 2 °C was observed, the cooling capacity of the system reduced by an average of 0.25 kW or 6.7 %, while the COP reduced by 3.9%. Subsequently, in the third stage of results, the performance results were obtained similar to the modified system (R134a/R744 with gas-cooler), concluding that the proposed fluids (R513A and R1234yf) for direct drop-in of R134a in a cascade system with R744, have an energy similarity ensuring the effectiveness of substitution. Regarding the environmental analysis to the alternative systems, the TEWITOTAL for Brazil, presented a reduction of approximately 36% for the R513A/R744 pair and 59% for the R1234yf/R744 pair, which is the best drop-in option for a subcritical cascade system with R744.